2021
DOI: 10.1089/acm.2021.0184
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Chiropractic Care in Providing Health Promotion and Clinical Preventive Services for Adult Patients with Musculoskeletal Pain: A Clinical Practice Guideline

Abstract: Objective: To develop evidence-based recommendations on best practices for delivery of clinical preventive services by chiropractors and to offer practical resources to empower provider applications in practice.Design: Clinical practice guideline based on evidence-based recommendations of a panel of practitioners and experts on clinical preventive services.Methods: Synthesizing the results of a literature search for relevant clinical practice guidelines and systematic reviews, a multidisciplinary steering comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 112 publications
0
9
0
Order By: Relevance
“…Claims for the use of wellness-based chiropractic for health require evidence. At present there is little evidence for primary prevention in MSK conditions [ 52 ] and particularly in MSK low back pain [ 53 ], so it may be challenging for wellness-based chiropractors to create evidence for primary prevention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Claims for the use of wellness-based chiropractic for health require evidence. At present there is little evidence for primary prevention in MSK conditions [ 52 ] and particularly in MSK low back pain [ 53 ], so it may be challenging for wellness-based chiropractors to create evidence for primary prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, claims currently outstrip evidence in this area and it remains a key goal for this group to validate their claims. A recent best practice guideline in chiropractic health promotion is recommended as a possible way forward [ 52 ]. The challenge to the wellness group will be to find evidence to support the teaching of any prevention strategies in evidence-based wellness practitioner training programs.…”
Section: Introductionmentioning
confidence: 99%
“…By nature of training and scope, chiropractors also address public health issues and supportive measures for healthy human development during the clinical encounter. 20 These may include advice regarding injury prevention, healthy diet, physical activity needs, sleep advice, reduced screen time (including mobile/cell phone use), healthy social relationships, and vigilance around childhood trauma. 21–23 It has been found that, in general, children with a decreased health-related quality of life have higher utilization of complementary and integrative medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Chiropractors may have a role in preventing IPV if they have appropriate screening tools. 6 A chiropractors' knowledge and skills in recognizing IPV is likely to affect their clinical reasoning, decisionmaking, and clinical outcomes. Furthermore, they are obliged to comply with clinical and legal responsibilities.…”
Section: Introductionmentioning
confidence: 99%